Newly Discovered Adipokines: Pathophysiological Link Between Obesity and Cardiometabolic Disorders - Kim, Jung A.; Choi, Kyung Mook (Frontiers in Physiology, 2020)
With the increasing prevalence of obesity, obesity-related problems such as cardiometabolic disorders (CMD), are also rapidly increasing. To prevent and alleviate the progressive course of CMD, it is important to discover the pathophysiological mechanisms between obesity and CMD. Adipose tissue is now recognized as an active endocrine organ that releases adipokines. Adipokines play a pivotal role in chronic low-grade inflammation, oxidative stress, and impaired insulin signaling, contributing to metabolic derangement and leading to CMD. Recent studies have provided substantial evidence for supporting the association between adipokines and CMD. In this review, we highlight the pathophysiological action of adipokines in CMD that includes metabolic syndrome, type 2 diabetes, non-alcoholic fatty liver disease, and cardiovascular diseases. We focused on translational and clinical research of novel adipokines associated with metabolic and cardiovascular regulation. Exploration of the role of these adipokines connecting obesity and CMD may provide a perspective on adipokine-based therapeutic implications for CMD.